2017
DOI: 10.1016/j.ssci.2015.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Safety-in-numbers: A systematic review and meta-analysis of evidence

Abstract: This paper presents a systematic review and meta-analysis of studies that have estimated the relationship between the number of accidents involving motor vehicles and cyclists or pedestrians and the volume of motor vehicles, cyclists and pedestrians. A key objective of most of these studies has been to determine if there is a safety-in-numbers effect. There is safety-in-numbers if the number of accidents increases less than proportionally to traffic volume (for motor vehicles, pedestrians and cyclists). All st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
110
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(117 citation statements)
references
References 24 publications
4
110
1
2
Order By: Relevance
“…31 If only bicycle exposure is modelled (ie, not including the five control variables), the coefficient is equal to 0.37 and 0.33 in the two periods, respectively, which are comparable with other studies regardless of the spatial scale they used. This suggests that controlling other variables may help better evaluate the effect of bicycle exposure.…”
Section: Discussionsupporting
confidence: 79%
“…31 If only bicycle exposure is modelled (ie, not including the five control variables), the coefficient is equal to 0.37 and 0.33 in the two periods, respectively, which are comparable with other studies regardless of the spatial scale they used. This suggests that controlling other variables may help better evaluate the effect of bicycle exposure.…”
Section: Discussionsupporting
confidence: 79%
“…Our estimates were much lower than those reported by Elvik and Bjørnskau,20 suggesting a stronger SIN effect.…”
Section: Resultscontrasting
confidence: 92%
“…In the third place, nearly all studies of safety-in-numbers rely on cross-sectional data, which make it difficult to establish causal relationships. In a recent review, Elvik and Bjørnskau (2016) concluded that no studies of safety-in-numbers have controlled adequately for all relevant confounding variables and that one cannot conclude that these studies have uncovered a causal relationship.…”
Section: Introductionmentioning
confidence: 99%